Annual plant reviews, Volume 46: Oceanography and Marine Biology - Gibson, R (CRC Press, 2009)
Increasing interest in marine biology and its relevance to environmental issues creates a demand for authoritative reviews of recent research. Oceanography and Marine Biology has addressed this demand for nearly 40 years. This annual review considers basics of marine research, special topics, and emerging new areas. Regarding the marine sciences as a unified field, the text features contributors who are actively engaged in biological, chemical, geological, and physical aspects of marine science. This edition includes a full color insert and covers such topics as the ecological status of the Great Barrier Reef, the effects of coral bleaching on fisheries, and the biology of octopus larvae.